84 Left atrial reverse remodelling in dilated cardiomyopathy. (8th December 2021) - Nuzzi, Vincenzo; Raafs, Anne; Manca, Paolo; Henkens, Michiel T.h.M.; Gregorio, Caterina; Boscutti, Andrea; Verdonschot, Job; Hazebroek, Mark; Knackstedt, Christian; Merlo, Marco; Stolfo, Davide; Sinagra, Gianfranco; et al.
Abstract: Aims: Left atrial (LA) dilation is associated a with worse prognosis in several cardiovascular settings but therapies can promote LA reverse remodelling. Characterizing and defining the prognostic implications of LA volume (LAVI) reduction in dilated cardiomyopathy (DCM). Methods and results: Consecutive DCM patients from two tertiary care centres, with available echocardiography at baseline and at 1 year follow-up, were analysed. LA dilation was defined as LAVI >34 ml/m 2, Delta (Δ)LAVI was defined as the 1 year relative LAVI reduction. The outcome was a composite of death/heart transplantation/heart failure hospitalization (D/HTx/HFH). Five hundred sixty patients were included [age 52 ± 13 years; left ventricular ejection fraction (LVEF) 31 ± 10%, LAVI 45 ± 18 ml/m 2 ]. Baseline LAVI had a non-linear association with the risk of D/HTx/HFH, independently from LVEF ( P < 0.001). At 1 year follow-up, LAVI decreased in 374 patients (67%, median ΔLAVI 24%, interquartile range 37% 11%). Factors independently associated with ΔLAVI were higher baseline LAVI and lower baseline LVEF. After adjustment for confounders, ΔLAVI showed a linear association with the risk of D/HTx/HHF (HR: 0.92, 95% CI: 0.86 0.99 per 5% decrease, P < 0.001). At 1 year Follow-up, patients with a ≥ 15% reduction in ΔLAVI or LAVI normalization (i.e. Follow-up LAVI ≤34ml/m2) (42% of the cohort) were at lower risk of D/HTx/HFH (HR: 0.49, 95% CI: 0.33 0.74, P < 0.001). Conclusions: In a large cohort of DCM, 1 year reduction in LAVI is observed in the majority of patients. The association between reduction in LAVI and D/HTx/HHF candidates LA reverse remodelling as complementary early therapeutic goal in DCM.